Effects of UTAUT 2 Model on the Use of BCA Mobile Banking in Indonesia - et. al., Aniek Susilowati, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Purpose – The m-banking service is a long-distance transaction platform that is innovative and strategic product provided by financial institution. It has succeeded in removing physical limitation of banking activities through the use of mobile device by customers. Support for the advance in internet technology bringing about considerable and continuous changes in banking operational have enabled customers to connect with business world and make transaction at any time, so that it also changes how customers use banking services. The World’s Best Bank has positioned BCA as a bank capable of adapting to pandemic situation because its banking services related to technology is considered as the best. Therefore, this research recognizes the need for testing factors affecting BCA customers to adopt and continue to use BCA m-banking service. Design/methodology/approach – the conceptual relationship of behavior intention on the acceptance and the use of information technology in this research used UTAUT2 model. Primary data were processed using SEM method with SMART-PLS software collected from survey questionnaires carried out to 400 respondents having BCA accounts and using BCA m-banking in the last 3 months. Findings – the main factors such as habit, hedonic motivation and facilitating condition were found to provide significant effect on behavior intention of customers to adopt and use BCA m-banking service. Practical implications – the findings are expected to educate public about m-banking service capable of facilitating banking transaction and recommending banking system to provide a safe m-banking service and it also requires sustainable development.